Reflection of electromagnetic waves in inhomogeneous medium (MAUSAM, 1970)
Reflection coefficient and. impedence of electromagnetic waves in a stratified layered medium following mathematical laws compatible with the propagation conditions associated with the diurnal and seasonal variations, have been deduced.